Advances in Condition Monitoring of Railway Infrastructure - Araliya Mosleh; Diogo Ribeiro; Abdollah Malekjafarian; Maria D. Martínez-Rodrigo (Sensors, 2024)
In recent years, there has been a notable surge in investments directed towards developing new railway lines and revitalising existing ones, reflecting a global commitment to enhance transportation infrastructure [...]